The effect of electron beam irradiation on preparation of sago starch/polyvinyl alcohol foams - Wongsuban, Benchamaporn; Muhammad, Kharidah; Ghazali, Zulkafli; Hashim, Kamaruddin; Ali Hassan, Muhammad (Elsevier B.V., 2003)
Blends of sago starch (SS)/polyvinyl alcohol (PVA) were irradiated with doses ranging from 10 to 30 kGy. Foams were then produced from these irradiated blends using a microwave. Changes in the degree of crosslinking, gel strength, thermal stability morphology of blends and linear expansion of foam with increasing irradiation doses were subsequently investigated. It was observed that the degree of crosslinking was important in maximizing the positive effect on foams produced. The gel strength of SS/PVA blends was affected by the irradiation. The crosslinking by the irradiation enhanced the thermal stability of SS/PVA blends. The results also revealed that the highest linear expansion of foams could be produced by irradiation blends at 15 kGy. Changes in blend morphology were observed upon irradiation. © 2003 Elsevier B.V. All rights reserved.